2019
DOI: 10.3390/ijms20040914
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single CpG Demethylation on the Pattern of DNA-Protein Binding

Abstract: Epidermal differentiation is a complex process and its regulation may involve epigenetic factors. Analysis of DNA methylation in 20 selected regions within the epidermal differentiation complex (EDC) gene cluster by targeted next-generation sequencing (NGS) detected no or only minor changes in methylation, mostly slight demethylation, occurring during the course of keratinocyte differentiation. However, a single CpG pair within the exon of the PGLYRP3 gene underwent a pronounced demethylation concomitant with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Results of the latter analysis revealed a stable methylation landscape and a lack of correlation between the methylation status and gene expression level. This finding was in agreement with earlier studies focused on genes of the Epidermal Differentiation Complex (EDC), which maintained their methylation status throughout the differentiation of primary keratinocytes despite large changes in expression [ 26 , 27 ]. This may indicate that the impact of DNA methylation on epidermal differentiation is exerted at the early stage, probably deciding on the balance between proliferation/quiescence of progenitor cells, with a lesser effect on gene expression in keratinocytes already poised for differentiation.…”
Section: Epigenetic Mechanisms Involved In Epidermal Differentiationsupporting
confidence: 92%
“…Results of the latter analysis revealed a stable methylation landscape and a lack of correlation between the methylation status and gene expression level. This finding was in agreement with earlier studies focused on genes of the Epidermal Differentiation Complex (EDC), which maintained their methylation status throughout the differentiation of primary keratinocytes despite large changes in expression [ 26 , 27 ]. This may indicate that the impact of DNA methylation on epidermal differentiation is exerted at the early stage, probably deciding on the balance between proliferation/quiescence of progenitor cells, with a lesser effect on gene expression in keratinocytes already poised for differentiation.…”
Section: Epigenetic Mechanisms Involved In Epidermal Differentiationsupporting
confidence: 92%
“…In fact, its single demethylation site corresponds to its expression in CD4+ T cells [60]. Finally, prominent demethylation of a single cytosine residue situated in the 5th exon of the PGLYRP3 gene is associated with an increment of mRNA level of PGLYRP3 [61]. This information supports our hypothesis that a single demethylation in one specific CpG dinucleotide could reactivate the gene.…”
Section: Discussionsupporting
confidence: 64%
“…To obtain undifferentiated HaCaT cells the medium was exchanged for DMEM without calcium (Life Technologies-Thermo Fisher Scientific, Waltham, MA, USA) supplemented with calcium-free 10% FBS as described in [21], and the cells were cultured in these conditions for at least 14 days. Primary human keratinocytes, NHEK (PromoCell, Heidelberg, Germany), were cultured in Keratinocyte Growth Medium 2 (PromoCell, Heidelberg, Germany) with growth supplement as described in [16]. To induce differentiation of NHEKs and of undifferentiated HaCaT cells the respective culture media were supplemented with 1.8 mM CaCl 2 (final concentration) and the cells were cultured for 72 h.…”
Section: Cell Culturementioning
confidence: 99%
“…Epigenetic regulation through DNA methylation, histone modifications, and miRNA activity may also be involved in this process [13]. Initial studies on DNA methylation of gene promoters revealed clear differences between undifferentiated and differentiated keratinocytes [14], although many gene promoters and putative regulatory regions within EDC were shown to maintain their methylation status during differentiation [15,16]. Lack of major changes in DNA methylation within EDC and elsewhere in the genome was recently confirmed by a genome-wide methylation analysis of in vitro differentiating keratinocytes [17].…”
Section: Introductionmentioning
confidence: 99%